Are My Neighbours Ageing Yet? Local Dimensions of Demographic Change in German Cities - Uwe Neumann (Journal of Population Ageing, 2013)
Among the highly developed countries, demographic ageing is particularly advanced in Germany. Accentuated by migration, there is great regional variation in the progress of demographic change. Within urban areas, residential neighbourhoods differ considerably in their demographic composition and perspectives. Based on municipal data, this paper examines regional variability in the diversity and pace of neighbourhood-level ageing. Focusing on the Rhine-Ruhr conurbation in North Rhine-Westphalia, the analysis outlines at what pace ageing proceeds in a variety of neighbourhoods, which attract no constant influx of working-age migrants. After decades of suburbanisation, in the period from 1998 to 2008 regional migration concentrated on the central districts of large cities. More profoundly in the most prosperous cities growing in population than in other cities, childless working-age adults separate from other age groups and family types in selected central city quarters. The findings suggest that spatial differentials in ageing are likely to affect future location decisions and, thereby, regional and local prosperity.
Keywords: 330; Demographic change; Neighbourhoods; Segregation; Migration